Anarchy, Commercialism, and "Publish or Perish" - Altbach, Philip; Rapple, Brendan (International Higher Education, 2012)
The business of academic journals has become deeply flawed. Many new and unneeded journals have been founded by fake publishers seeking to make quick money. Some of the established publishers have raised prices to an unsustainable level. Technology creates both problems and possibilities.